Pathophysiologic Insights from Biomarker Studies in Neurological Disorders - Ruck, Tobias; Moccia, Marcello; Warnecke, Tobias; Bittner, Stefan (Frontiers Media SA, 2020)
Neuroimmunological and neurodegenerative disorders are major healthcare issues associated with high individual and socioeconomic burden. For many neurological disorders an early diagnosis is key for efficient management and therapy. However, neural tissues from brain, spinal cord or peripheral nerves are difficult to obtain, and their extraction is often associated with functional deficits. Therefore, in most cases a combination of biomarkers such as radiologic or biochemical findings are used to define a diagnosis in the clinical practice. The development of pathologically-sensitive and easy-to-measure disease biomarkers is a key factor for investigating new medications in phase 2 trials aiming to quickly screen their efficacy, and in phase 3 trials where they are coupled to clinical measures. Moreover, biomarkers are used to predict treatment efficacy and adverse event risk, paving the way for personalized medicine with individual risk assessment and prevention strategies. In the last few decades the enormous technological progress, especially omics technologies, expanded the definition of biomarkers from biochemical and clinical by genetic, proteomic, metabolic or microbial markers. Interestingly, some of the biomarker studies additionally provided important insights into the pathophysiology of neurological disorders. In multiple sclerosis TNF-blocking drugs can promote onset or exacerbation of MS and GWAS (genome-wide association studies) data informed about the underlying mechanisms instructing clinical practice. In Parkinson's disease (PD), evaluation of Lewy pathology provided new pathophysiological insights attributing PD pathology progression to a prion-like process starting in the gastrointestinal tract. However, many other suggested biomarkers remain solely correlative, often lacking a causative link to the underlying disease mechanisms possibly explaining their lack in sensitivity and specificity.